Detection of SARS-CoV-2-independent immunoregulatory activity of COVID-19 convalescent plasma - Brox, Regine; Achenbach, Susanne; Hackstein, Holger (Transfusion, 2021)
Background: Convalescent plasma has emerged as a potential specific treatment for coronavirus disease 2019 (COVID-19), since it contains severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies. Several studies are currently investigating the efficacy of convalescent plasma for treatment of COVID-19, with a focus on neutralizing antibodies. However, there is little information on whether convalescent plasma may contain additional immunoregulatory constituents produced by the blood donor during convalescence. Therefore, using a standardized whole blood assay employing synthetic toll-like receptor (TLR) ligands, we have investigated the immunoregulatory capacity of convalescent plasma in direct comparison to ABO-matched allogeneic control plasma. Study design and methods: Whole blood samples from healthy blood donors were collected, and autologous plasma was replaced by convalescent plasma or ABO-matched control plasma. Standardized innate immune triggering and monitoring was performed by adding different TLR ligands (Pam3CsK4 [TLR1/2], HKLM [TLR2], LPS [TLR4], flagellin [TLR5], ssRNA40 [TLR8], imiquimod [TLR7], and FSL-1 [TLR2/6]) and subsequent quantitative analysis of pro- and anti-inflammatory cytokines (IP-10, IL-1β, TNF-α, MCP-1, IL-6, IL-10, and IFN-γ) by cytometric bead array. Negative controls included unstimulated samples as well as samples spiked with autologous plasma. Results: COVID-19 convalescent plasma (CCP) significantly decreased pro-inflammatory cytokines production triggered by different TLR ligands in healthy donors as compared with healthy control plasma. IL-6, MCP-1, and IFN-γ represented the cytokines that are most frequently downregulated by convalescent plasma. Conclusion: Our experiments reveal a potential novel, SARS-CoV-2-independent immunomodulatory activity of CCP, which may be beneficial for COVID-19 patients.
CRIS-Team Scopus Importer:2021-10-22
Keywords: convalescent plasma; COVID-19